2009
DOI: 10.1007/s10495-009-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and apoptosis: liver

Abstract: The liver is a central regulator of glucose homeostasis and stores or releases glucose according to metabolic demands. In insulin resistant states or diabetes the dysregulation of hepatic glucose release contributes significantly to the pathophysiology of these conditions. Acute or chronic liver disease can aggravate insulin resistance and the physiological effects of insulin on hepatocytes are disturbed. Insulin resistance has also been recognized as an independent risk factor for the development of liver inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 154 publications
(161 reference statements)
2
32
0
Order By: Relevance
“…NAFLD and insulin resistance have been associated with occurrence of hepatocyte apoptosis [4,33,34]. In particular, our group has previously shown that caspase-3 and (c) adipose tissue.…”
Section: Discussionmentioning
confidence: 89%
“…NAFLD and insulin resistance have been associated with occurrence of hepatocyte apoptosis [4,33,34]. In particular, our group has previously shown that caspase-3 and (c) adipose tissue.…”
Section: Discussionmentioning
confidence: 89%
“…Crosstalk between proteins relevant to insulin resistance and hepatocellular injury, including tumor necrosis factor (TNF), nuclear factor κB (NF-κB), and JNK, has been proposed as a potential driver of apoptosis in the liver (Schattenberg and Schuchmann, 2009). Indeed, apoptosis is associated with severe hepatocellular injury and steatohepatitis (Guicciardi and Gores, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Which have provided a new insight into the pathophysiology of IVDD [4][5][6][7]. Apoptosis is the process of programmed cell death (PCD) that is involved in cell deletion during organogenesis and in controlling cell proliferation and differentiation in adult tissues, as well as in the pathogenesis of various diseases [8][9][10]. Apoptosis of disc cells plays an important role in the degenerative process [11], which leads to a decrease in cell density [4,12] and extracellular matrix (ECM) degradation [7,12].…”
Section: Introductionmentioning
confidence: 99%